BRONCHOPULMONARY DYSPLASIA IS A RISK FACTOR IN THE RESPIRATORY SYNCYTIAL VIRUS INFECTION IN CHILDREN - D.Yu. Ovsyannikov (Union of pediatricians of Russia, 2009)
Bronchopulmonary dysplasia, originally described as iatrogeny in extreme premature infants who had long-term artificial pulmonary ventilation, is currently viewed as a chronic lung disease in children. With the onset in the neonatal period, at an older age bronchopulmonary dysplasia is characterized by persisting respiratory symptoms, hospital readmissions due to an intensifying broncho-obstructive syndrome, the related etiological factor of which is respiratory syncytial virus. The review using evidence from current professional sources provides information about epidemiology, etiology, pathogenesis and pathomorphology, the clinical picture and diagnostics of bronchopulmonary displasia and contribution of respiratory syncytial virus to disease exacerbation. The up-to-date classification of disease is provided. Approaches to therapy and prevention are characterized from the standpoint of evidence-based medicine.Key words: bronchopulmonary dysplasia, respiratory syncytial virus, children.